Best proximity point results in set-valued analysis - Choudhury, Binayak S. S.; Maity, Pranati; Metiya, Nikhilesh (Nonlinear Analysis: Modelling and Control, 2016)
Here we introduce certain multivalued maps and use them to obtain minimum distance between two closed sets. It is a proximity point problem which is treated here as a problem of finding global optimal solutions of certain fixed point inclusions. It is an application of set-valued analysis. The results we obtain here extend some results and are illustrated with examples. Applications are made to the corresponding single valued cases.